Making Mongol history : Rashid al-Din and the Jamiʻ al-tawarikh - Kamola, Stefan T. (Edinburgh studies in classical Islamic history and culture., 2019)
"This book examines the life and work of Rashid al-Din Tabib (d. 1318), the most powerful statesman working for the Mongol Ilkhans in the Middle East. It begins with an overview of administrative history and historiography in the early Ilkhanate, culminating with Rashid al-Din's Blessed History of Ghazan, the indispensable source for Mongol and Ilkhanid history. Later chapters lay out the results of the most comprehensive study to date of the manuscripts of Rashid al-Din's historical writing. The complicated relationship between Rashid al-Din's historical and theological writings is also explored, as well as his appropriation of the work of his contemporary historian, 'Abd Allah Qashani."--Back cover